Inhibition of p53 protects placental trophoblast from hydrogen-peroxide induced apoptosis. (7th June 2011) - Sharp, A N; Crocker, I P; Baker, P N; Heazell, A E P
Abstract : Introduction: Pre-eclampsia is characterised by exaggerated placental apoptosis and p53 over-expression. This is hypothesised to result from the generation of reactive oxygen species (ROS) secondary to placental ischaemia-reperfusion. Hydrogen peroxide (H2 O2 ) has been used to represent ROS and has been shown to induce apoptosis and p53 expression in placental villous explants. Might inhibition of p53 with pifithrin-α arrest placental damage due to ROS in pre-eclampsia? Methods: Term villous explants were exposed to 1000 µM H2 O2 and 10 µM pifithrin-α for 48 h (total culture 96 h). Tissue was wax embedded and apoptosis and trophoblast turnover assessed by M30 antibody recognition to cleaved cytokeratin-18 and syncytial knot formation, respectively. Apoptosis was also assessed by caspase-3/7 activity from protein. Real-time PCR was performed for p53, p21, Mdm2, Puma and Bax. Results: Treatment with H2 O2 increased apoptosis as measured by caspase-3/7 activity (p<0.01, Friedman, n=5) and M30 (p<0.01, Friedman, n=5). Syncytial knot formation was also increased by exposure to H2 O2 (p<0.01, Friedman, n=5). Both apoptosis and syncytial knot formation was reduced by treatment with Pifithrin-α. Exposure to H2 O2 increased p53, p21 and Puma mRNA expression (p<0.05, Friedman, n=5), but had no effect on Mdm2 or Bax. Again, this increase was reduced with Pifithrin-α. Conclusion: Treatment of placental tissue with H2 O2 increases apoptosis and gene expression in the p53 pathway. This effect is reduced by treatment with the p53 inhibitor pifithrin-α, suggesting that H2 O2 induces p53-mediated apoptosis which is reversible with p53 inhibition. Inhibition of the p53 pathway could be a therapeutic target for placental-related pathologies.